The impact of Nehemiah leadership and relevance in leadership of Arastamar Theology High School - Ming, David; Titik Windarti, Maria; Lontoh, Terifena Julien (Technium Social Sciences Journal, 2021)
The present state of leadership crisis is no different from that of Nehemiah's day. At that time the Israelites were in a state of oppression, being transported to Babylon as slaves in a foreign power until Persia came to power. The exiles were finally allowed to return to their homeland. The nation of Israel was in great trouble and in a disgraceful state (Nehemiah 1: 3). In such conditions the Israelites did not have a leader figure who could and would want to lead and assist the Israelites in overcoming existing problems from a spiritual, political, social, and economic perspective. The Israelites live without leadership like sheep without a shepherd. This is where the leadership crisis lies. This paper uses the Historical - Descriptive research method, this method aims to support the search for data on the theory of Nehemiah's leadership role as a leader who succeeded in building the walls of Jerusalem within 52 days. The conclusion of the analysis shows that Nehemiah's leadership is visionary and inspirational. Leadership relevant to the management of the Arastamar Theological College (SETIA